Perbandingan Akad-Akad yang digunakan Perbankan Syariah di Malaysia dan Indonesia - Fitri Hidayati J. (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Andalas, 2024)
Differences in ulama views have implications for the use of Islamic banking contracts in Malaysia and Indonesia. The purpose of this article is to discuss the contracts used in Islamic banking in Malaysia and Indonesia. The method used in this article is a literature review, digging deeply from existing literacy sources. Comparison of contracts on Islamic banking products in Malaysia and Indonesia can be seen in Islamic banking products including, funding in Malaysia and Indonesia both use Wadiah and Mudharabah contracts. Financing in Malaysia uses Murabahah, Ba'I Bithaman Ajil (BBA), Ijarah, Ijarah Thumma, and Bai contracts, while in Indonesia it uses Murabahah, Mudharabah, Musyarakah, Mudharabah wal Murabahah, Salam, Istishna, Ijarah Muntahiy Bittamlik (IMBT), Qardh, Rahn, and Hawalah contracts. In banking services Malaysia uses Qardh Hasan, BBA, Bai'al-Inah, and Ujr contracts, while Indonesia uses Ujr, Sarf, Kafalah, Wakalah, and Mudharabah Muqayyadah contracts. While Islamic financial instruments in Malaysia use Baial-Inah, BBA, Murabahah, Mudharabah, and Ujr contracts, while Indonesia uses Wadiah and Mudharabah contracts. Finally, there are variable rate banking products that use Ijarah, Kafalah, Wakalah, Bai alInah, Bai'al-Dayn, Istishna contracts but in Indonesia there are no banking products.